PENGEMBANGAN MODUL LAJU REAKSI BERBASIS PEDAGOGICAL CONTENT KNOWLEDGE (PCK) UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Frisca Zahrona Utami Harahap; Destria Roza (Universitas Negeri Medan, 2020)
This study aims to analyze the feasibility of the PCK Chemistry module and learning outcomes on the subject matter of the reaction rate taught by the PCK Chemistry module class XI MAN 1 Medan Medan. The selected sample is class XI MIA 3 as an experimental class. The method used in this research is R&D. The module analysis results state that the average overall validation result is 3.65 which means that the module is feasible to use. While the results of the module analysis based on the respondents obtained an average of 3.70 which means that the developed PCK module is appropriate to use. This is also evidenced from student learning outcomes that are taught using the PCK chemistry module. Hypothesis testing is done by using the t-one party test that is the right side, with the results of this study at a significance level of 5% (α = 0.05) indicating that tcount> t table (12.63> 1.68) then Ho is rejected. Thus, showing chemistry learning outcomes using the PCK chemistry module is greater or equal to KKM, where an average pretest of 28.25 is obtained and an average of posttest is obtained an average of 86.04.